RESEARCH OF A MULTI - STAGE RECEIVER OF A LASER MICROPHONE - Rayimdjanova Odinakhon Sodiqovna; Iskandarov Usmonali Umarovich (Journal Park Publishing, 2023)
Currently, optical systems are used in different fields of human society very widely. The relevance that the systems depend on optical receivers and transmitters, where the visible and not visible rays of lasers were used. And the laser signal returns from the reflected object very weak and it is required to strengthen and accept it for processing. To do this, we need accurate transmission and receiving systems. This research is directed to use multi –stage sound amplification systems in to the laser microphone.
Keywords: laser microphone. sound amplification, multi–stage, optical systems, cascade, receiver, transmitter.